2016
DOI: 10.4269/ajtmh.15-0270
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Risk Factors of Inkoo Virus in Northern Sweden

Abstract: The mosquito-borne Inkoo virus (INKV) is a member of the California serogroup in the family Bunyaviridae, genus Orthobunyavirus. These viruses are associated with fever and encephalitis, although INKV infections are not usually reported and the incidence is largely unknown. The aim of the study was to determine the prevalence of anti-INKV antibodies and associated risk factors in humans living in northern Sweden. Seroprevalence was investigated using the World Health Organization Monitoring of Trends and Deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Results from the diagnostic test in use show cross-reactions between the serogroup viruses. Most (82%) of the acute infections in this study were INKV cases, confirmed by using PRNT, which showed >4-fold titer differences, consistent with findings that INKV is the major California serogroup agent in seroprevalence studies in Finland and Sweden ( 33 ). Although most cases seem subclinical or mild, the data in our study indicate that the clinical disease may occasionally be severe; all children with acute illness had INKV infection and were hospitalized.…”
Section: Discussionsupporting
confidence: 90%
“…Results from the diagnostic test in use show cross-reactions between the serogroup viruses. Most (82%) of the acute infections in this study were INKV cases, confirmed by using PRNT, which showed >4-fold titer differences, consistent with findings that INKV is the major California serogroup agent in seroprevalence studies in Finland and Sweden ( 33 ). Although most cases seem subclinical or mild, the data in our study indicate that the clinical disease may occasionally be severe; all children with acute illness had INKV infection and were hospitalized.…”
Section: Discussionsupporting
confidence: 90%
“…For example, Oc. hexodontus (Evander et al 2016) occur only in the boreal areas. The distributions of the mammalian hosts (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…JCV is thought to be amplified in a transmission cycle involving wild ungulates such as white-tailed deer and a variety of mosquito species, while for SHV the reservoir hosts are small mammals such as hares, squirrels and chipmunks [9][10][11][12][13]. High seroprevalence rates have been reported for both viruses in different wild mammal species from North America [14][15][16][17][18][19][20], suggesting that natural transmission cycles can be highly effective in maintaining CSGV activity. However, there has been little effort to assess which types of environment present a high risk of exposure to these viruses.…”
Section: Introductionmentioning
confidence: 99%